Building an Archival Database for Visualizing Historical Networks. A Case for Pre-Modern Korea - Seungmin Paek; Jong Hee Park; Sangkuk Lee (Historical Life Course Studies)
In this paper, we share the experience of collecting and organizing pre-modern Korean historical materials into a searchable digital archive. The Ajou Interdisciplinary Research Group (AIRG) has continuously collected historical data of pre-modern Korea for the past 10 years to assist the study of family history, historical demographics, and social mobility. This paper describes the rich data sources for historical studies of Korea, such as household registers, genealogies, and state examination registers, and we summarize contributions to the study of historical demography and related fields.